Carcinosarcoma of parotid gland - A rare case report (Indian Journal of Case Reports, 2016)
Carcinosarcoma (true malignant mixed tumor) is an extremely rare tumor of the salivary gland. It is a biphasic tumor and is composed of both malignant epithelial and malignant mesenchymal component. Commonly, squamous cell carcinoma and adenocarcinoma forms the epithelial component and chondrosarcoma forms the mesenchymal component. We, hereby, report a parotid lesion in a 47 year old female that contained adenocarcinoma as epithelial component and chondrosarcoma as mesenchymal component. We report this unusual case of carcinosarcoma of parotid gland due to its rarity. It mimics benign lesions on ultrasonographic examination. On fine needle aspiration, the diagnosis of carcinosarcoma can be missed, as was in our case where it was reported as pleomorphic adenoma with atypical features. Histopathology only gives confirmatory diagnosis. In addition, a short review of literature along with possible pathogenesis of malignant mixed tumor of salivary gland is also presented.